To the problem of life origin on the Earth - Mykhailiuk, V. P. (History of science and technology, 2015)
Considering the issue of life origin on the Earth, we will briefly recollect about the biosphere, living substance and its biogeochemical functions discovered by V. I. Vernadskyi. Human interaction with the environment has not caused significant changes in biosphere during many hundred years of human generations, however all this time there has been an accumulation of knowledge and forces. Gradually, using his intellectual advantage over the other members of the animal world, a human being reached out to the entire upper shell of the planet - the whole biosphere. This activity has led to the domestication of animals, to the cultivated plants’ removal. A human being began changing the world and create for himself a new wildlife that has never existed on the planet.